After effects of military service and training in a soldier’s life - Maduwanthi, AA Ishari; Buddike, W Dinesh (Electronic Journal of Education, Social Economics and Technology, 2023)
This paper reviews the possible after-effects of military training given by the Sri Lankan Army to recruits and to existing army personnel who would like to be promoted to the next stage of the hierarchy. It is considered that training personnel is a major task in Sri Lankan Army as the military promotes from within and develops its leaders rather than selecting them from outside their ranks. Therefore, the process of training is expensive, yet it is one of the country’s topmost priorities since army personnel ensures the necessary security schemes in Sri Lanka while maintaining an anti-terror stance. In order to gather the required data, a questionnaire with 15 questions was provided to six retired army personnel who had served below the lieutenant position in Sri Lanka Army. Additionally, those people were interviewed with another set of interview questions in order to find out the differences between the answers they have given in the questionnaire in comparison to the interview. This paper seeks to answer the question of whether there are any after-effects the army personnel experience due to the rigorous training provided by the Sri Lankan Army even after their service period is completed. It also examines whether these effects are positively or negatively related to their daily experiences. It is hoped this study will inform the general public and the ones who are currently serving in the military about the consequences of military training.